النهر الصناعي ودوره في تحقيق الاستدامة المائية في ليبيا - صالح أمهني; حسن دواس; عبدالله بن إدريس; نجيب بن موسى (The Libyan Journal of Science, 2024)
The aim of this study is to focus on the role of the Man Made River Project (MMRP) in the resolvingand the mitigating of the crucial water shortfall in Libya. An Analytical descriptive program was utilized to achieve these goals.Libya is considered to be one of the poorest counties in regard to the availability of renewable water resources. However, enormous volumes of groundwater in reservoirs are located in the southern part of Libya and hence it was necessary to transport the water from the south to the more populated areas in the north. It was concluded that the MMRP provided water for more than 70% of Libyan cities and therefore,it was the ideal solution for the water supply issue to meet the increasing demand for the agricultural, household and industrial purposes. Since the main water supply in Libya is from a non- renewable source, it is necessary to take all the necessary measures to maintain and protect this precious source of life. Such measures include continuous maintenance, sabotage prevention, and public awareness and searching for alternatives sources of water to reduce the burden on the MMRP .